1984
DOI: 10.1039/f19848002889
|View full text |Cite
|
Sign up to set email alerts
|

Salt effects on the cloud point of the poly(ethylene oxide)+ water system

Abstract: The cloud point of high-molecular-weight poly(ethy1ene oxide), PEO, in aqueous salt solution has been determined as a function of the salt concentration for all potassium halides, alkali-metal chlorides and alkali-metal hydroxides. Our theoretical model for the pure PEO +water system (J. Chem. Soc., Faraday Trans. I, 1981, 77, 2053) has been extended to include the effects of salt on the phase separation. Basic features of the present model are a hydration shell with enhanced structuring of water as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
212
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(258 citation statements)
references
References 1 publication
18
212
0
Order By: Relevance
“…16 depends upon the valency and hydration of the ions as well as specific interactions of the ions with the ether oxygens of PEG. It is thus expected from the Gibbs free energy of hydration (∆Ghyd) that Na + has a salting-out effect stronger than that of K + , although Florin et al 16 have shown that the difference in the salting-out ability is very small between the two ions. The ∆Ghyd values for Na + and K + are -375 and -304 kJ/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 depends upon the valency and hydration of the ions as well as specific interactions of the ions with the ether oxygens of PEG. It is thus expected from the Gibbs free energy of hydration (∆Ghyd) that Na + has a salting-out effect stronger than that of K + , although Florin et al 16 have shown that the difference in the salting-out ability is very small between the two ions. The ∆Ghyd values for Na + and K + are -375 and -304 kJ/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have studied the influence of the type of inorganic salts on the phase separation of aqueous PEG solutions, [13][14][15][16][17][18] and have suggested that the stronger is the hydration of the ion, the lower is the concentration required to form a two-phase system.…”
Section: Resultsmentioning
confidence: 99%
“…5) [8]. According to Florin's analysis [25], this phenomenon would be related to the influence of salt on the water structure around the PEO macromolecules. For most of the salt studied (Fig.…”
Section: Concept and Designmentioning
confidence: 99%
“…This is surprising since it is known that anions are less hydrated than cations [21]. The salt effect is thus not due to a water competition effect but must be related to how the ions interact with the solute water interface [18,22,23]. This reasoning is based on surface tension measurements [24,25] which show that anions are repelled from a dielectric discontinuity like the water/air or the water/oil interface in the order F-> Cl-> Br-> I-.…”
Section: Effect Of Sodium Chloridementioning
confidence: 99%